An overview of deploying membrane bioreactors in saline wastewater treatment from perspectives of microbial and treatment performance. (November 2022) - Cao, Thanh Ngoc-Dan; Bui, Xuan-Thanh; Le, Linh-Thy; Dang, Bao-Trong; Tran, Duyen Phuc-Hanh; Vo, Thi-Kim-Quyen; Tran, Huu-Tuan; Nguyen, Thanh-Binh; Mukhtar, Hussnain; Pan, Shu-Yuan; Varjani, Sunita; Ngo, Huu Hao; et al.
Graphical abstract: Highlights: Various membrane bioreactors have been applied to treat the saline wastewaters. The increase of salinity significantly influences on systems' treatment performance. Biodiversity in the MBRs is eliminated with the elevated salt concentrations. Behavior of microorganisms under different salinity levels is discussed. Abstract: The discharged saline wastewater has severely influenced the aquatic environment as the treatment performance of many wastewater treatment techniques is limited. In addition, the sources of saline wastewater are also plentiful from agricultural and various industrial fields such as food processing, tannery, pharmaceutical, etc. Although high salinity levels negatively impact the performance of both physicochemical and biological processes, membrane bioreactor (MBR) processes are considered as a potential technology to treat saline wastewater under different salinity levels depending on the adaption of the microbial community. Therefore, this study aims to systematically review the application of MBR widely used in the saline wastewater treatment from the perspectives of microbial structure and treatment efficiencies. At last, the concept of carbon dioxide capture and storage will be proposed for the MBR-treating saline wastewater technologies and considered toward the circular economy with the target of zero emission.